Giant Abdominal Lipoma in Adult - Cinar Ozcan, Nihal (Case Rep Surg, 2021)
Lipomas arising from the omentum are extremely rare in adults. Omental lipomas are typically asymptomatic, but very large ones may cause nonspecific abdominal symptoms and discomfort. Rarely they can cause omental torsion and present with an acute abdomen. We report a 41-year-old female patient with a giant lipoma (40 × 26 × 8 cm and 11,520 g) who presented with mild abdominal discomfort. Workup included abdominal ultrasound (USG) and magnetic resonance imaging (MRI). Surgical resection was performed without complication. No recurrence was observed during 4-year follow-up.